A NOVEL ISOPARAMETRIC FINITE-ELEMENT DISPLACEMENT FORMULATION FOR AXISYMMETRICAL ANALYSIS OF NEARLY INCOMPRESSIBLE MATERIALS - Yu, H; Houlsby, G; Burd, H (1993)
The theoretical formulation of a new six-noded isoparametric displacement finite element, which is well studied for elastic- plastic analysis of axisymmetric constrained solids by using a rational displacement interpolation function, is presented in this paper. The proposed displacement interpolation function, is presented in this paper. The proposed displacement interpolation function implies that the displacement in the axial direction and the product of the displacement in the radial direction and the radius should be treated as two independent basic variables. Alternatively, the proposed displacement interpolation function can also be implemented in a conventional displacement formulation simply by using a modified shape function matrix. The suitability of the proposed formulations simply by using a modified shape function matrix. The suitability of the proposed formulations is first studied theoretically by assessing the number of degrees of freedom pre constraint and then verified by performing numerical experiments on typical boundary value problems which involve incompressible behavior.